The Efficiency of Government Expenditure : Experiences From Africa - Honjo, Keiko; Gupta, Sanjeev; Verhoeven, Marijn (Washington, D.C. : International Monetary Fund, 1997)
This paper assesses the efficiency of government expenditure on education and health in 38 countries in Africa in 1984-95, both in relation to each other and compared with countries in Asia and the Western Hemisphere. The results show that, on average, countries in Africa are less efficient than countries in Asia and the Western Hemisphere; however, education and health spending in Africa became more efficient during that period. The assessment further suggests that improvements in educational attainment and health output in African countries require more than just higher budgetary allocations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet